Adsorption of bovine serum albumin on Zr co-sputtered a-C(:H) films: implication on wear behaviour - Escudeiro, A. (2014)
The use of protective coatings in biomedical field is an ongoing scientific challenge. Among different materials, carbon-based coatings are considered a potential surface treatment for orthopaedic implants. In this study, the effect of Zr incorporation in amorphous carbon coatings on the wear behaviour under protein containing lubrication was investigated. The coatings were deposited by dc unbalanced magnetron sputtering in Ar (non-hydrogenated) and Ar+CH4 (hydrogenated) discharges onto Ti based biomedical substrate. To improve the adhesion between the film and substrate a functional gradient Ti based layer was deposited (~550 nm). The surface wettability was evaluated to assess the effect of the Zr and hydrogen content. The films with Zr were found to be hydrophobic enhancing the protein adsorption onto the surface; no significant differences were found when H was incorporated in the films. The adsorption layer characterized by X-ray photoelectron spectroscopy showed a well defined nitrogen peak originating from the organic layer. The tribological properties of the film were evaluated by unidirectional pin-on-disc testing with diluted bovine serum lubrication and physiological solution at 37±3 C°. The friction and the wear of the coatings were very low compared to uncoated substrates in both lubrication conditions. The ability of the surfaces to adsorb proteins was considered as the driving force for wear resistance acting as a protecting layer. In addition, the incorporation of Zr decreased the wear of the counterbody (Ti alloy) due to higher albumin adsorption.